Production of new polymeric materials from kraft lignin - Vieira, Fernanda Rosa (2021)
The growing interest in the complete or at least partial replacement of petroleum-derived polymers by renewable ones is a common trend towards sustainable economy. Among the polymers from renewable resources, lignin is a natural aromatic irregular polymer, widely available from the kraft black liquor that so far has been mainly burned for energy production. Kraft lignin is very attractive for the development of polyurethanes (PU) upon being oxyalkylated, which increases its added value and can contribute to a more sustainable development. Briefly, in the present work kraft lignin, isolated via the LignoBoost process, was oxyalkylated using propylene carbonate (PC), and the ensuing lignin-based polyol (LBP) was explored as counterpart in the formulation of new PU materials, namely foams and adhesives. After a detailed chemical and structural characterization of the LignoBoost lignin from Eucalyptus globulus used as a renewable raw material, the oxyalkylation process with PC was thoroughly studied regarding the effect of catalysts and other process parameters (time, temperature and quantify of PC) on the quality of LBP. In addition, a Design of Experiments (DoE) was applied to optimize this process towards the production of crude LBP with suitable hydroxyl number (IOH) and viscosity to be used in the preparation of rigid polyurethane foams (RPUF) and PU adhesives This optimization led to a reduction in the amount of PC in the process and to increase the lignin content in crude LBP from 12.5 up to 25. 0% (w/w). Moreover, a methodology to obtain LBP with a lignin content as higher than 25% was later developed. In a following stage, the use of crude LBP in the formulation of RPUF for thermal insulation, PU adhesive and functional composites was explored. Once more, the DoE was used to investigate the effect of the main components in the formulation of RPUF with the aim of producing lightweight bio-based RPUF with low thermal conductivity to be used as a potential thermal insulator material in building construction. The statistical data analysis showed that thermal conductivity and density of RPUF are highly influenced by the content of crude LBP and blowing agent (BA). Furthermore, it was also concluded that the crude LBP has a negative effect on the cell morphology and thermal stability. Yet, the optimization allowed to obtain RPUF using 100% of crude LBP in the formulation which upon fine tuning the type and quantities of BA and surfactant yielded a RPUF which meet the market requirements for application as thermal insulation material in building construction. Specifically, the optimized formulation yielded a bio-based RPUF with low thermal conductivity (0.0289 W/ m. K), low density (33.2 kg/m3) and adequate compressive stress resistance (127 kPa). Furthermore, the use of LBP enhanced the fire resistance of the RFUF as confirmed by cone calorimeter tests. These results proved that lignin- based RPUF is competitive with conventional RPUF. Concomitantly, PU adhesives were developed using 100 % of crude LBP in the formulation, where the effect of the NCO/OH ratio on its properties was studied and compared with those of a commercial PU adhesive (CPA). It was found that the lignin-based PU adhesive presented better chemical resistance and adhesion efficiency than CPA using less polyisocyanate in the formulation. Despite some lower thermal stability and shorter gelation time of lignin-based PU adhesive when compared to those of the CPA, overall, the results have shown it can be an interesting alternative to reduce the use of petroleum-derived polyols and isocyanates. Having optimized the preparation of RPUFs and of PU adhesives derived from oxyalkylated kraft lignin, a dip coating methodology was used to produce conductive bio-based RPUFs using PEDOT: PSS solution. This methodology led to an increase of the electrical conductivity by up to 10 orders of magnitude and a stretchability enhancement of almost 50% hence, it may find potential application in devices for the Internet of Things (IoT).